2013
DOI: 10.1093/cercor/bht028
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the Dyslexia-Associated Gene Kiaa0319 Impairs Temporal Responses to Speech Stimuli in Rat Primary Auditory Cortex

Abstract: One in 15 school age children have dyslexia, which is characterized by phoneme-processing problems and difficulty learning to read. Dyslexia is associated with mutations in the gene KIAA0319. It is not known whether reduced expression of KIAA0319 can degrade the brain's ability to process phonemes. In the current study, we used RNA interference (RNAi) to reduce expression of Kiaa0319 (the rat homolog of the human gene KIAA0319) and evaluate the effect in a rat model of phoneme discrimination. Speech discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
89
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 90 publications
7
89
0
1
Order By: Relevance
“…12 and 13), as predicted from previous single and multiunit studies (Atencio and Schreiner 2012;Cheung et al 2001;Eggermont et al 2011) and subcortical stations of the auditory pathway (Rodriguez et al 2010a(Rodriguez et al , 2010b. Our study builds on these prior studies because we demonstrated that reliable, phase-locked responses to sound features can be generated from ECoG-level signals.…”
Section: Discussionsupporting
confidence: 64%
“…12 and 13), as predicted from previous single and multiunit studies (Atencio and Schreiner 2012;Cheung et al 2001;Eggermont et al 2011) and subcortical stations of the auditory pathway (Rodriguez et al 2010a(Rodriguez et al , 2010b. Our study builds on these prior studies because we demonstrated that reliable, phase-locked responses to sound features can be generated from ECoG-level signals.…”
Section: Discussionsupporting
confidence: 64%
“…An increasing number of studies have investigated the function of RD risk genes in animal models [2][3][4][5][6][7][8][9][10][11][12][13], and the neurobiological and behavioral consequences of genetic RD risk variants in humans [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], motivating the need for a synthesis of these findings, especially because they relate to emerging avenues of human research on the role of neurochemistry [32] and neural oscillations [33][34][35][36] in RD. Here, we present a timely integration of diverse lines of current research linking some of the key neural and behavioral deficits associated with RD to basic neural processes.…”
Section: Premise Of the Neural Noise Hypothesismentioning
confidence: 99%
“…As shown schematically in Figure 2B, increased glutamatergic activity disrupts the excitation-inhibition balance of cortical neurons, decreasing the precision of spike timing and increasing neural noise. Another RD risk gene homolog, Kiaa0319, has also been associated with greater trial-by-trial firing rate variability in response to speech and nonspeech sounds and with increased neural excitability in primary auditory cortex [10].…”
Section: Glutamatergic Signalingmentioning
confidence: 99%
See 2 more Smart Citations